Hoja
de ejercicios de matemáticas
(-2)
– (-10) = ______ 7
– (-6) = ______
(7
– 3 = ______ 7
– 0 = ______
2
+ 6 = ______ 10
+ 10 = ______
5
– (-9) = ______ (-6)
– (-9) = ______
(-6)
+ 2 = ______ 1
– (-9) = ______
(-9)
+ 2 = ______ (-10)
– (-10) = ______
(-2)
+ 10 = ______ 4
– 2 = ______
10
– 8 = ______ (-2)
– (-7) = ______
11
+ 13 = ______ 10
+ (-13) = ______
13
+ (-1) = ______ 10
+ (-6) = ______
(-12)
– (-14) = ______ (-2)
– (-4) = ______
1
– (-10) = ______ (-11)
– (-15) = ______
8
+ (-11) = ______ (-14)
– (-15) = ______
(-6)
– (-14) = ______ 11
+ (-12) = ______
0
+ 9 = ______ (-8)
– (-13) = ______
(-5)
– (-5) = ______ 12
– 5 = ______
No hay comentarios:
Publicar un comentario